2020
DOI: 10.1186/s13063-020-04300-7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sitting at work: process evaluation of the SMArT Work (Stand More At Work) intervention

Abstract: Background: Office-based workers accumulate high amounts of sitting time. Stand More At Work (SMArT Work) aimed to reduce occupational sitting time and a cluster randomised controlled trial demonstrated it was successful in achieving this aim. The purpose of this paper is to present the process evaluation of the SMArT Work intervention. Methods: Questionnaire data were collected from intervention participants at 6 months (n = 58) and 12 months (n = 55). Questionnaires sought feedback on the different component… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
5
23
0
Order By: Relevance
“…These were followed by short feedback sessions where the results were explained to each participant. Although not part of the intervention, these health assessments did reportedly have an impact on awareness and knowledge about a healthy lifestyle in both groups, which is consistent with other research [ 17 ]. This was an unintended outcome of the study, which although did not lead to behavioural changes in control participants, did provide participants with a more holistic understanding of their current health status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These were followed by short feedback sessions where the results were explained to each participant. Although not part of the intervention, these health assessments did reportedly have an impact on awareness and knowledge about a healthy lifestyle in both groups, which is consistent with other research [ 17 ]. This was an unintended outcome of the study, which although did not lead to behavioural changes in control participants, did provide participants with a more holistic understanding of their current health status.…”
Section: Discussionsupporting
confidence: 89%
“…All participants were asked to complete questionnaires 1 month after the baseline health assessment and 1 month after the six-month follow-up health assessment, using a combination of multiple choice, open-ended, and Likert scale questions. At baseline, the questionnaires sought feedback about the baseline health assessment (although not part of the intervention, previous research has shown that being measured as part of the evaluation can have an impact on participants’ lifestyle [ 17 ]. The intervention follow-up questionnaire sought feedback about the quality, dose, and usefulness of each component of SHIFT (i.e., the education sessions, cab workout equipment, Fitbit, step challenges, text message feedback), and any other lifestyle or work changes that may have impacted the results.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from physical health outcomes, however, future intervention developers should also consider the emerging evidence on sedentary behaviour and psychological outcomes (De Cocker et al, 2020). For example, standing seems to play a positive role in increasing alertness and boost productivity (Biddle et al, 2020), which is particularly relevant to University students.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reveals that people with more active jobs had lower all-cause or cardiovascular disease mortality risk than those with jobs that involved mostly sitting [26]. A large-scale prospective cohort study in 220,000 Australians published an association between sitting and all-cause mortality across sexes, age groups, body mass index and physical activity levels [27]. Despite knowing how harmful it is to our health, we spend most of our daily time sitting.…”
Section: Home-based Teleworking Sedentary Lifestyle and Ideal Posturesmentioning
confidence: 99%
“…They are intended to contribute to weight control/loss through additional energy expenditure, relief and prevent musculoskeletal pain (acute and chronic), and improve cardiometabolic health (e.g., adjustable sit-stand desktops). Workplace interventions that promote standing breaks and sit-stand adjustable workstations show improvements in health markers and increase work productivity, efficiency and collaboration among employees [27,31,32]. Although stand-up working at the computer doubles the energy expenditure over the 8 h workday and is a good alternative [33], the focus of healthy computer working has been put on preventing spine-related health problems derived from erroneous sitting postures.…”
Section: Home-based Teleworking Sedentary Lifestyle and Ideal Posturesmentioning
confidence: 99%